Foundations of voice studies : an interdisciplinary approach to voice production and perception - Kreiman, Jody.; Sidtis, Diana (Malden, MA : Wiley-Blackwell, 2011)
'Exploring questions of how and why the quality of a person's voice influences our perceptions, Foundations of Voice Studies provides a comprehensive introduction to, and analysis of, the multifaceted role that voice quality plays in our social lives. Beginning with an approachable and thorough overview of various aspects of vocal physiology and its control, Kreiman and Sidtis examine the neurological and sociological contexts for producing and listening to voices. Replete with fascinating sidebars and discussions of how voices are used in advertising and media, and legal and forensic issues of identifying voices, they have written an essential work that unifies the results of their own pioneering studies with the most current scientific literature. This unique and interdisciplinary volume on all facets of voice production and its perception is supported by sound files and additional material, available at www.wiley.com/go/voicestudies'--
Machine generated contents note: 1 Introduction. -- 2 Producing a voice and controlling its sound. -- 3 Neurological foundations of production and perception of voice. -- 4 Physical characteristics and the voice. -- Can we hear what a speaker looks like? -- 5 Recognizing speaker identity from voice. -- Theoretical and ethological perspectives and a psychological model. -- 6 The brain behind the voice. -- Cerebral models of voice production and perception. -- 7 Identifying unfamiliar voices in forensic contexts. -- 8 Linguistic uses of voice quality. -- How voice signals linguistic and pragmatic aspects of communication -- 9 Perception of emotion and personality from voice. -- 10 Miscellany. -- Voice in singing, media, and the law.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- phonology; Voice -- Social aspects; Sociolinguistics; LANGUAGE ARTS & DISCIPLINES / Linguistics / Phonetics & Phonology